2015
DOI: 10.1016/j.jnucmat.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and surface orientation on migration behaviours of helium atoms near tungsten surfaces

Abstract: Molecular dynamics simulations were performed to study the dependence of migration behaviours of single helium atoms near tungsten surfaces on the surface orientation and temperature. For W{100} and W{110} surfaces, He atoms can quickly escape out near the surface without accumulation even at a temperature of 400 K. The behaviours of helium atoms can be well-described by the theory of continuous diffusion of particles in a semi-infinite medium. For a W{111} surface, the situation is complex. Different types of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The DFT-calculated mechanical properties showed a Young’s modulus of 229 GPa, which is in good agreement with the experimental nanoindentation measurements. High hardness in a metallic film can be related to the enhanced grain boundary strengthening from nanocrystallinity. , The deposited RHEA film dominates in the (110) plane due to its relatively low diffusivity with increasing film thickness as compared to the (200) and (211) planes resulting in nanocrystalline grains. , Therefore, the dislocation movement is hindered within the columnar grains during plastic deformation . Furthermore, the high entropic effect, sluggish diffusion, and lattice distortion in RHEA films contribute to the measured high hardness and Young’s modulus .…”
Section: Resultsmentioning
confidence: 99%
“…The DFT-calculated mechanical properties showed a Young’s modulus of 229 GPa, which is in good agreement with the experimental nanoindentation measurements. High hardness in a metallic film can be related to the enhanced grain boundary strengthening from nanocrystallinity. , The deposited RHEA film dominates in the (110) plane due to its relatively low diffusivity with increasing film thickness as compared to the (200) and (211) planes resulting in nanocrystalline grains. , Therefore, the dislocation movement is hindered within the columnar grains during plastic deformation . Furthermore, the high entropic effect, sluggish diffusion, and lattice distortion in RHEA films contribute to the measured high hardness and Young’s modulus .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that trap mutation reactions easily occur on the W(111) surface. 14,15 In our studies on the behaviors of He diffusion toward the surface, the He escaping behavior is affected by the trap mutation on the W(111) surface. As shown in Fig.…”
Section: Diffusion Of He Toward the Surfacementioning
confidence: 94%
“…Crystal surface is an important type of defect, which will affect many physical processes such as fracture, adsorption, corrosion, catalysis, crystal growth, radiation, etc. [1][2][3][4][5][6]. Surface energy, one of the most important quantities in surface science, is still difficult to determine experimentally for clean surface and just few data exist [7][8][9].…”
Section: Introductionmentioning
confidence: 99%